Progress in molecular biology and translational science. - Chakravarti, Debabrata (Progress in molecular biology and translational science, 2009)
Regulatory Mechanisms in Transcriptional Signaling, volume of Progress in Molecular Biology and Translational Science, includes in-depth discussion on roles of Chromatin remodeling proteins in nuclear receptor signaling, and ANCCA regulator in cancer. This important resource, edited by Dr. Debabrata (Debu) Chakravarti, offers research on the progesterone receptor action in leiomyoma and endometrial cancer and emerging roles of the ubiquitin protein system in nuclear hormone receptor signaling, in order to provide the reader with expert discussions of up-to-date research.